L'injure comme délit. L'approche des fuqahâ' théologiens-légistes musulmans - Yahya Ould al-Barra; Abdel Wedoud Ould Cheikh (Revue des Mondes Musulmans et de la Méditerranée)
This text focuses on how Moslem legal scholars deal with a singular form of verbal aggression called qadhf. It deals with charges of illicit sexual intercourse, particularly when the charges are against free Moslem women of good moral character, never previously charged for any specific offence. The study of this type of infringement reveals the close links between insult and sexuality and more precisely, with female sexuality, controlled as it is by the principle of the reproduction of the corporate groups organized along patrilineal lines ('aṣabât) on which the Arab-Moslem social order is based. Insults, in the context of the qadfthemes, take the form of threats, precisely because, by questioning female sexuality, it affects the honor of the individuals and the groups, i.e. the synthetic principle of classification of men within the society such as the fuqahâ' see it.